Identification of Soilborne Pathogenic Fungi in Sorghum Plantations at the Center for Agricultural Modernization Implementation in South Sulawesi - Putri kayla Putnarubun; Yulis Sayang; Eka lestari ariyanti (Universitas Merdeka Pasuruan, 2026)
sorghum (Sorghum bicolor (L) Moench) is a cereal crop with significant potential as an alternative source of food, feed, and industrial material. However, sorghum productivity is not yet maximized due to pest and disease attacks. Soil-borne pathogenic fungi are common pests that can reduce yields by 20.93%-51.17%. Therefore, identification is needed to determine the types of soil-borne pathogens in the rhizosphere, providing basic information about their presence in sorghum crops. The research was conducted at the Agricultural Modernization Application Center (BRMP) in Maros Regency, South Sulawesi Province, and the Plant Protection Laboratory of the Islamic University of Makassar, from September to December 2025. The initial procedure involved taking samples from five diagonal locations using a 30 cm pipe. PDA media was prepared to grow microorganisms, followed by serial dilutions and purification three times to prevent contamination. The final step was identifying the samples on the PDA media. Identification results showed three genera of soil fungi: Aspergillus sp (saprophytic), Beauveria sp (saprophytic), and Fusarium sp (soil-borne pathogen) in sorghum crops.